2003
DOI: 10.1186/1475-2891-2-16
|View full text |Cite
|
Sign up to set email alerts
|

Understanding why adult participants at the World Senior Games choose a healthy diet

Abstract: Background: Identifying those seniors most likely to adopt a healthy diet, the relative importance they place on certain perceived benefits associated with a healthy diet, and whether these perceived benefits are associated with selected demographic, lifestyle, and health history variables is important for directing effective dietary health promotion programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Previous research using the TPB to predict seniors' intentions and behavior also found that perceived behavioral control was an important factor to consider (10,11,19) According to a farmers' market study by Kunkel et al (13) some of the reasons seniors did not attend the farmers' market was lack of available transportation and inconvenient times. If seniors feel as though they are unable to attend a farmers' market, the likelihood of them having intentions to purchase fresh fruits and vegetables at farmers' markets might be low.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous research using the TPB to predict seniors' intentions and behavior also found that perceived behavioral control was an important factor to consider (10,11,19) According to a farmers' market study by Kunkel et al (13) some of the reasons seniors did not attend the farmers' market was lack of available transportation and inconvenient times. If seniors feel as though they are unable to attend a farmers' market, the likelihood of them having intentions to purchase fresh fruits and vegetables at farmers' markets might be low.…”
Section: Discussionmentioning
confidence: 95%
“…Research has shown that attitude, SN, and PBC are significant predictors of intention and behavior (9)(10)(11). Studies involving senior citizens have found that PBC was the most significant factor in health intentions and behavior (10)(11).…”
Section: Senior Citizensmentioning
confidence: 97%
See 3 more Smart Citations